2003
DOI: 10.1053/jhep.2003.50418
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction-mediated intercellular communication in a long-term primary mouse hepatocyte culture system

Abstract: Gap junction-mediated intercellular communication (GJIC) is critical for maintaining integral cellular processes including differentiation and growth control. The disruption of GJIC has been correlated with aberrant function in many cell types, including hepatocytes in vivo; therefore it is imperative that cellular model systems support intercellular communication to simulate normal cellular functions. Functional GJIC has been shown in long-term primary rat hepatocyte cultures, which have been implemented wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
(58 reference statements)
2
18
0
Order By: Relevance
“…The presence of connexin proteins in liver is associated with normal liver function. The induction of Cx32 and Cx26 proteins in DMSO-containing primary mouse hepatocytes cultures was also observed and confirmed the importance of connexin proteins in differentiating hepatocytes (Stoehr & Isom, 2003). In the present study, Cx32 was shown to be expressed in hepatocytes maintained in KDS culture medium for up to 3 weeks (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…The presence of connexin proteins in liver is associated with normal liver function. The induction of Cx32 and Cx26 proteins in DMSO-containing primary mouse hepatocytes cultures was also observed and confirmed the importance of connexin proteins in differentiating hepatocytes (Stoehr & Isom, 2003). In the present study, Cx32 was shown to be expressed in hepatocytes maintained in KDS culture medium for up to 3 weeks (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…primary hepatocytes were allowed to form extensive cell-cell contacts in solution, multicellular spheroids were observed that preserved viability and metabolic activity over many weeks (Hamilton et al, 2001;Landry et al, 1985). The activation of signaling pathways resulting from hepatocyte contact can be mediated through membrane proteins (Corlu et al, 1991) or via gap junction communication (Stoehr and Isom, 2003). While the advantages of hepatocyte aggregates for in vitro culture are well known, this approach has been limited due to the lack of suitable technology for controlling the size and location of the spheroids.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatocytes were isolated from untreated HB-EGF WT male mice, 6–8 weeks of age, by a modification of previously described methodology (23). Hepatocytes were resuspended in DMEM containing 10% fetal bovine serum, 100 U/ml penicillin and 100 mg/ml streptomycin, plated on 60-mm BD Biocoat Collagen I Culture Dishes (BD Biosciences, Bedford, MA, USA), and maintained at 37°C in a humidified atmosphere of 5% CO 2 /95% air.…”
Section: Methodsmentioning
confidence: 99%